Lusutrombopag has slightly stronger effects on patients with mild thrombocytopenia compared with those with severe thrombocytopenia: A multicenter propensity score matching study. (8th January 2022) - Furuichi, Yoshihiro; Takeuchi, Hirohito; Uojima, Haruki; Atsukawa, Masanori; Arai, Taeang; Arase, Yoshitaka; Kako, Makoto; Hidaka, Hisashi; Itoi, Takao
Abstract: Background: Lusutrombopag effectively increases platelet count in patients with severe thrombocytopenia. However, no multicenter studies analyzing the effects of Lusutrombopag on patients with mild thrombocytopenia (platelet count > 50 000/µL) have been performed. In this study, we aimed to clarify the efficacy of Lusutrombopag on these patients by unifying background factors by propensity score matching. Methods: A total of 139 patients with thrombocytopenia were enrolled, and matched for age, sex, etiology, disease, treatment, liver function, renal function, peripheral blood count, and spleen index. The primary endpoint was to compare the increase in platelet count from baseline between the high‐platelet group (>50 000/µL) and the low‐platelet group (<50 000/µL) after Lusutrombopag treatment, using propensity score matching. The secondary endpoint was to clarify platelet transfusion avoidance rate and adverse events, moreover, to identify independent predictors associated with the increase in platelet count. Results: The mean increase in platelet count was 67 000/μL vs 48 000/μL in all patients (high‐ vs low‐platelet group, P  = .024), and 64 000/μL vs 48 000/μL ( P  = .12) after propensity score matching. The increase in platelet count and the platelet transfusion avoidance rate tended to be higher in the high‐platelet group. There was no significant difference between adverse events. Predictors associated with an increase in platelet count were sex, estimated glomerular filtration rate, and spleen index by multivariate analysis. Conclusion: Lusutrombopag has a little stronger effect in patients with mild thrombocytopenia than those with severe thrombocytopenia and showed a more substantial effect in patients with impaired renal function and small spleen. Abstract : Furuichi and colleagues clarified differences in the effect of lusutrombopag in chronic liver disease patients with mild and severe thrombocytopenia in a multicenter propensity score matching study. Lusutrombopag showed a stronger effect in patients with mild thrombocytopenia and a more substantial effect in patients with impaired renal function and small spleen.